TRIM32 Deficiency Impairs Synaptic Plasticity by Excitatory-Inhibitory Imbalance via Notch Pathway. (26th March 2020) - Ntim, Michael; Li, Qi-Fa; Zhang, Yue; Liu, Xiao-Da; Li, Na; Sun, Hai-Lun; Zhang, Xuan; Khan, Bakhtawar; Wang, Bin; Wu, Qiong; Wu, Xue-Fei; Walana, Williams; et al.
Abstract: Synaptic plasticity is the neural basis of physiological processes involved in learning and memory. Tripartite motif-containing 32 (TRIM32) has been found to play many important roles in the brain such as neural stem cell proliferation, neurogenesis, inhibition of nerve proliferation, and apoptosis. TRIM32 has been linked to several nervous system diseases including autism spectrum disorder, depression, anxiety, and Alzheimer's disease. However, the role of TRIM32 in regulating the mechanism of synaptic plasticity is still unknown. Our electrophysiological studies using hippocampal slices revealed that long-term potentiation of CA1 synapses was impaired in TRIM32 deficient (KO) mice. Further research found that dendritic spines density, AMPA receptors, and synaptic plasticity-related proteins were also reduced. NMDA receptors were upregulated whereas GABA receptors were downregulated in TRIM32 deficient mice, explaining the imbalance in excitatory and inhibitory neurotransmission. This caused overexcitation leading to decreased neuronal numbers in the hippocampus and cortex. In summary, this study provides this maiden evidence on the synaptic plasticity changes of TRIM32 deficiency in the brain and proposes that TRIM32 relates the notch signaling pathway and its related mechanisms contribute to this deficit.